SEROPREVALENCE OF HEPATITIS C AMONG THE APPARENTLY HEALTHYBLOOD DONORS OF KARACHI - Maeesa Wadood et al (Baqai Journal of Health Sciences)
Hepatitis C is a global health issue. Pakistan is among the prevalent countries for hepatitis C virus (HCV). Due to poverty, unemployment, low literacy rate, unawareness and poor health facilities, Pakistani population are susceptible to HCV transmission. As blood transfusion is a potential source of HCV; therefore, this study was designed to determine the recent seroprevalence of HCV among the healthy blood donors of Karachi, Pakistan. For this purpose, 536 blood donors were screened for antiHCV antibodies by 3rd generation ELISA. The seroprevalence of HCV observed is 2.99% among healthy blood donors. Male predominance is noticed with seropositivity of 2.62%; however, only 0.37% female blood donors were reactive for anti-HCV antibodies. This study concludes that HCV frequency has been increased in the natives of Karachi, Pakistan when compared to the past studies. Therefore, it is recommended that the healthcare authorities should play a vital role in enforcing preventive measures for HCV transmission.